Labour/Le Travail and Canadian Working-Class History: A View from Afar - Burgmann, Verity (Labour/Le Travailleur, 2002)
Abstract This article attempts to explain the similarities and parallels between Labour/ Le Travail and its Australian equivalent, Labour History; as well as analysing Labour/Le Travail';s distinctive interests and concerns, which reflect the peculiarities of the Canadian. It suggests, in particular, that the timing of Labour/Le Travail's appearance was propitious and that it was well positioned for various reasons to take advantage of the Thompsonian moment in labour historiography. Further, by responding to the rise of the new social movements, it was able to enrich further the study of labour history through attention to forms of oppression other than class. With class nonetheless remaining its central focus, a degree of political pessimism is understandably evident from the mid-1980s onwards, with the downturn in labour movement activity and allegations about the death of class. By the same token, signs of working-class remobilization in the late 1990s have encouraged a renewed sense of political purpose in the journal. It is argued that this situation also offers opportunities for new forms of dialogue between academics and activists challenging corporate globalization, enabling the journal and those associated with it to continue to reach out to audiences beyond the academy, to place their knowledge of labour's past at the service of movements contesting the current circumstances of the working class.